2019
DOI: 10.3389/fimmu.2019.02606
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Immune Activation in Systemic Lupus Erythematosus and the Autoimmune PTPN22 Trp620 Risk Allele Drive the Expansion of FOXP3+ Regulatory T Cells and PD-1 Expression

Abstract: In systemic lupus erythematosus (SLE), perturbed immunoregulation underpins a pathogenic imbalance between regulatory and effector CD4+ T-cell activity. However, to date, the characterization of the CD4+ regulatory T cell (Treg) compartment in SLE has yielded conflicting results. Here we show that patients have an increased frequency of CD4+FOXP3+ cells in circulation owing to a specific expansion of thymically-derived FOXP3+HELIOS+ Tregs with a demethylated FOXP3 Treg-specific demethylated region. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 57 publications
0
43
1
Order By: Relevance
“…The authors offered a hypothesis that reconciles human data showing that PTPN22 620W is a gain-of-function; PTPN22 620W allows chronic signaling through the TCR that drives T cell exhaustion, causing T cells from PTPN22 620R/W and PTPN22 620W/W donors to be less responsive to stimulation through the TCR—a finding reported by most studies. This is supported by evidence that expression of PD-1, a marker of T cell exhaustion, is enhanced on CD4 + T eff and T regs in healthy PTPN22 620W/W donors compared to healthy PTPN22 620R/R donors ( 74 ). Furthermore, the reduced calcium flux seen in PTPN22 620R/W donors was most notable in memory CD4 + T cells with no difference observed in naïve CD4 + T cells; this could indicate that the experienced population is exhausted ( 76 ).…”
Section: Regulation Of T Cell Function By Ptpn22 Allotypesmentioning
confidence: 79%
See 2 more Smart Citations
“…The authors offered a hypothesis that reconciles human data showing that PTPN22 620W is a gain-of-function; PTPN22 620W allows chronic signaling through the TCR that drives T cell exhaustion, causing T cells from PTPN22 620R/W and PTPN22 620W/W donors to be less responsive to stimulation through the TCR—a finding reported by most studies. This is supported by evidence that expression of PD-1, a marker of T cell exhaustion, is enhanced on CD4 + T eff and T regs in healthy PTPN22 620W/W donors compared to healthy PTPN22 620R/R donors ( 74 ). Furthermore, the reduced calcium flux seen in PTPN22 620R/W donors was most notable in memory CD4 + T cells with no difference observed in naïve CD4 + T cells; this could indicate that the experienced population is exhausted ( 76 ).…”
Section: Regulation Of T Cell Function By Ptpn22 Allotypesmentioning
confidence: 79%
“…Most studies report no differences in most CD4 + T cells subsets (i.e., T H 1, T H 17, T H 1T H 17, T FH ) ( 73 ). However, PTPN22 620W/W donors had slightly-increased FOXP3 + CD4 + regulatory T cells(T regs ) (7.94% vs. 6.76%) compared to donors with the common PTPN22 620R/R allotype ( 74 , 75 ). It has been reported that PTPN22 620R/W donors have increased memory CD4 + T cells when compared to PTPN22 620R/R donors (about 50% vs. 41% respectively) with a concomitant decrease in naïve CD4 + T cells ( 76 ).…”
Section: Regulation Of T Cell Function By Ptpn22 Allotypesmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 16 Conversely, PD-1 agonists have been proposed as therapies for autoimmune diseases. 17 Therefore, there is a need to gain a fuller understanding of the mechanisms of PD-1-mediated inhibition of T-cell signaling to improve the effects of PD-1 modulators in the clinic.…”
mentioning
confidence: 99%
“…Alternatively, CTLA4, which is highly expressed after T cell activation, acts as a competitor of CD28 and induces a state of T cell unresponsiveness and anergy (26)(27)(28). PD1, a novel co-inhibitory member of the B7/CD28 family, is engaged by PD-L1 to inhibit T cell activation (29)(30)(31). The PD1 inhibitor has been used in the clinical treatment of cancer to cancel the limitation on T cell-mediated anti-cancer responses (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%